Progress and Prospect of Thermoelectric Refrigeration - Cao Haishan (Zhileng xuebao)
Thermoelectric refrigeration is a solid-state refrigeration technology that uses electric energy to achieve refrigeration via the Peltier effect. Compared with vapor compression refrigeration, thermoelectric refrigeration offers the advantages of scalability, vibration-free, high reliability, and high temperature-control accuracy. Based on the development history and basic principles of thermoelectric refrigeration, this study focuses on the research progress of thermoelectric materials, refrigerator structures, functional layer interfaces, and heat sinks. Subsequently, applications of thermoelectric refrigeration are introduced based on their advantages. Finally, investigations regarding thermoelectric refrigeration are summarized and discussed.